Effect of Mannitol on Serum Electrolytes in Stroke Patients (Bangladesh Journal of Neuroscience, 2016)
Mannitol, an osmotic agent and a free radical scavenger with neuroprotective properties, have been reported in many studies to decrease cerebral oedema , infarct size and neurological deficit in patients with stroke. The present study was carried out in the Department of Pharmacology and Therapeutics in collaboration with the Departments of Medicine and Neurology of Sylhet M.A.G Osmani Medical College and Hospital to evaluate the effect of mannitol on serum electrolytes in stroke patients. A total number of Forty five (45) acute stroke patients were randomly allocated in two groups- 23 patients received mannitol and 22 patients did not receive mannitol. On Day 1 after measuring serum electrolyte levels of both groups, mannitol receiving group was given infusion mannitol 1 gm/kg IV bolus followed by 0.5 gm/kg IV 6 hourly till 3rd day and then again on Day 3 serum electrolyte levels of both groups were measured. Predisposing risk factors, egsmoking, hypertension, dyslipidaemia were also analyzed. RBS (Random Blood Sugar) and serum creatinine were estimated before treatment initiation with aim to assess hyperglycaemia and renal impairment respectively. Statistical analysis was done by SPSS program using unpaired ‘t’ test between two groups and between Day 1 and Day 3 by paired ‘t’ test. The result showed that serum sodium and potassium at Day 1 and Day 3 were almost similar between mannitol receiving group and mannitol non-receiving group ( P>0.05 for each component). After infusion of mannitol till third day, no electrolyte imbalance was noted. The study depicts that mannitol can be safely given to stroke patients as there were no change in electrolyte balance till third day.Bangladesh Journal of Neuroscience 2016; Vol. 32 (1): 21-27